Ru/g-C3N4 as an efficient catalyst for selective hydrogenation of aromatic diamines to alicyclic diamines. Issue 28 (25th April 2020) - Cao, Junya; Han, Fenggang; Wang, Liguo; Huang, Xiaoyu; Cao, Yan; He, Peng; Yang, Huanhuan; Chen, Jiaqiang; Li, Huiquan
Abstract : A series of Ru/g-C3 N4 materials with highly dispersed Ru were firstly prepared by an ultrasonic impregnation method using carbon nitride as a support. Abstract : A series of Ru/g-C3 N4 materials with highly dispersed Ru were firstly prepared by an ultrasonic impregnation method using carbon nitride as a support. The catalysts were characterized by various techniques including BET and elemental analysis, ICP-AES, XPS, XRD, CO2 -TPD and TEM. The results demonstrated that Ru/g-C3 N4 materials with a mesoporous structure and highly dispersed Ru were successfully prepared. The chemo-selective hydrogenation of p -phenylenediamine (PPDA) to 1, 4-cyclohexanediamine (CHDA) over Ru/g-C3 N4 as a model reaction was investigated in detail. PPDA conversion of 100% with a CHDA selectivity of more than 86% could be achieved under mild conditions. It can be inferred that the carbon nitride support possessed abundant basic sites and the Ru/g-C3 N4 - T catalysts provided suitable basicity for the aromatic ring hydrogenation. Compared to the N-free Ru/C catalyst, the involvement of nitrogen species in Ru/g-C3 N4 remarkably improved the catalytic performance. In addition, the recyclability of the catalyst demonstrated that the aggregation of Ru nanoparticles was responsible for the decrease of the catalytic activity. Furthermore, this strategy also could be expanded to the selective hydrogenation of other aromatic diamines to alicyclic diamines.